Sleep patterns in the pantaneira population (Research, Society and Development, 2021)
Introduction: sleep is vital, characterized as a set of behavioral and physiological changes. The research was carried out in a rural, isolated, Pantanal population, residing in the largest floodplain on the planet. Objectives: To identify sleep patterns in the Pantanal population. Method: Quantitative, descriptive, analytical, cross-sectional and comparative study, the total sample was 789 participants, distributed in rural (25%) and urban (75%) populations. For the analysis, descriptive statistical methods were used, with proportions estimation and corresponding standard error of the mean. The univariate analysis consisted of comparing proportions using the chi-square test and comparing means. Adjustment to normal distribution was assessed using a non-parametric test. Results: There was a significant increase in the proportion of sleep disorders with increasing age, decreasing with increasing level of education. Sleep changes occurred in a greater proportion among women, among those who have schooling up to high school, who have a greater number of children. Conclusion: The dissemination of these findings is essential for the promotion of the integral health of the Pantanal, aiming to overcome problems related to sleep and quality of life.